Complete Genome Classification System of Rotavirus alphagastroenteritidis: An Updated Analysis - Ricardo Gabriel Díaz Alarcón; Karina Salvatierra; Emiliano Gómez Quintero; Domingo Javier Liotta; Viviana Parreño; Samuel Orlando Miño (Viruses)
Rotavirus alphagastroenteritidis is the major causative agent of acute gastroenteritis in both children under the age of 5 and young mammals and birds globally. RVAs are non-enveloped viruses with a genome comprising 11 double-stranded RNA segments. In 2008, the Rotavirus Classification Working Group pioneered a comprehensive and complete RVA genome classification system, establishing a specific threshold, which measures the genetic distances between homologous genes. The aim of this study was to perform an updated systematic analysis of the genetic variability across all RVA genes. Our investigation involved assessing the established cutoff values for each RVA genome segment and determining the need for any updates. To achieve this objective, multiple sequence alignments were constructed for all 11 genes and one for each genotype with discrepancies. Also, pairwise distances along with their cutoff values were evaluated. The analyses provided insights into the current relevance of cutoff values, which remain applicable for the majority of genotypes. In conclusion, this study fortifies the current classification system by highlighting its robustness and accurate genotyping of Rotavirus alphagastroenteritidis.